Design of Traffic Monitoring System Based on Video Detection - Hong, Yu (Journal of physics. Conference series, 2019)
Traffic monitoring system is an important means to ensure the safe operation of traffic. According to the characteristics of road traffic monitoring environment, a real-time traffic monitoring system is designed by using image processing, computer vision, pattern recognition and other technologies. Experiments show that the system can effectively detect various typical traffic incidents and traffic operation parameters, and provide a favorable guarantee for traffic safety.